The incense trade during the Islamic period - Le Maguer, Sterenn (Proceedings of the Seminar for Arabian Studies, 2015)
This paper deals with the incenses that were traded and used in the Islamic world from the seventh to the sixteenth century. Many researches and publications deal with the ancient incense trade, but only a few focus on this trade during the Islamic period. This paper aims to present the results obtained from a multidisciplinary methodology. To identify the main substances used as incense, medieval Arabic sources such as the Kitāb al-nabāt written by Al-Asmaʿī and Abū Ḥanīfah al-Dīnawarī, or Ibn al-Bayṭār’s al-Jāmi li-mufradāt al-adwiyyah wa-l-aghdhiyyah are of great interest. These textual sources are compared to modern botanical studies and chemical analyses of the substances found in archaeological contexts. This allows us to map the distribution of these materials in order to establish the main trade routes across the Indian Ocean and the Arabian Peninsula. This research offers a new perspective on the commercial relations between the eastern Mediterranean world and the Indian Ocean through the Arabian Peninsula and its bordering seas in the medieval Islamic world.